KEDUDUKAN FATWA TERHADAP DASAR HUKUM PENYELESAIAN SENGKETA EKONOMI SYARIAH MELALUI BASYARNAS - Nunung Rodliyah; Nila Nargis; Abdur Rohman Husen (Postgraduate State Islamic Institute (IAIN) Metro, 2019)
The role of fatwa in supporting the implementation and implementation of sharia law in Indonesia is very diverse, for example in the implementation of contract agreements. Ideal contract in the contract of national sharia In language, the word